Play Determinants Influencing Acquisition of Numeracy Skills Among Early Childhood Learners in ECDE Centres in Kathiani Sub-County, Machakos County - Muema, Mary Mbula (My University, 2018)
This study sought to underscore the influence of play determinants in the teaching of Mathematics, particularly acquisition of numeracy skills among children in pre-school. The study was done in Kathiani zone which is in Kathiani Sub-County, Machakos County. Its purpose was to assess the influence of play determinants on acquisition of numeracy skills in Early Childhood Development and Education (ECDE) centres. In this regard, while focusing on pre-school institutions in Kathiani Sub-County the objectives of the study were threefold; to establish forms of play and how they influence acquisition of numeracy skills, to establish the criteria of material selection and how they influence acquisition of numeracy skills, and to establish teacher training and experience and how they influence pre-school learner‟s acquisition of numeracy skills among children in preschool institutions in Kathiani Sub-County. The study utilized qualitative research design. The dependent variable for the study was the acquisition of numeracy skills among children in pre-school institutions in Kathiani Sub-County, while independent variable is influence of play determinants. The target population comprised all pre-school children and pre-school teachers and headteachers in Kathiani Sub-County. The research instruments were piloted in two public schools and one private pre-school institution that were not included in the study sample, but within the target population. The data collected were edited and coded according to themes that emanated from the research objectives and questions. Questionnaire, interview schedules and observation schedules were used for data collection. Qualitative data were derived from open-ended responses received during interviews. The quantitative data were analyzed and presented using descriptive statistics such as frequency distribution, tables and percentages, and also in narrative form. Qualitative data were presented in narrative form. Majority (52.6%) of ECDE teachers agreed that they rarely consider quality when selecting play material. (63.2%) selecting play materials based on content enabled facilitation of acquisition of numeracy. Appropriateness is key when selecting play materials (52.6%) and (47.4%) of ECDE teachers indicated that selecting play materials based on sophistication has made it difficult for ECDE teachers to enhance acquisition of numeracy skills in ECDE centres in Kathiani Sub-County. The study further established that (39%) of ECDE teachers were not decided whether different forms of play enhanced acquisition of numeracy skills in ECDE Kathiani Sub-County. On training and experience of ECDE teachers, the study established 57.6% of ECDE teachers agreed that level of training influences delivery and acquisition of numeracy skills, (73.2%) teachers‟ mastery of content influences learners‟ acquisition of numeracy. Thus, the study recommended that ECDE teachers should be made to understand the importance of play in enhancing acquisition of numeracy skills in ECDE centres. ECDE teachers should undertake further proficiency training on planning, organizing and delivering of content in ECDE teaching and learning. It is expected that the findings of this study will contribute to the efforts towards early interventions to improve numeracy learning outcomes among learners in Kenya. The study is significant to the Ministry of Education, Kenya Institute of Curriculum Development, publishers and developers of early childhood education materials and teachers as well as owners and sponsors of ECDE institutions.